Penerapan Peramalan Penjualan Menggunakan Aplikasi POM QM pada produk Gula di PT. Pabrik Gula Candi Baru Sidoarjo - Moch. Kalam Mollah; Ahmad Dwi Saputra (Prosiding SENASTITAN: Seminar Nasional Teknologi Industri Berkelanjutan, 2022)
The rapidly changing business world and increasing competition from entrepreneurs require companies to be able to analyze the business environment and anticipate various opportunities that will arise in the future. Forecasting activities or future forecasts is one of the company's activities as the basis for making strategic business continuity decisions. PT. Candi Baru Sugar Factory is a subsidiary of PT. Rajawali Nusantara Indonesia (Persero) which produces SHS 1 type of sugar from sugar cane, the sugarcane milling capacity currently reaches 2,775 TCD. Inaccurate sales forecasting will lead to an increase in production costs, thereby reducing the efficiency of all investments. These problems can be used to predict the possibility of a decrease or increase in sales for a period of time in the future by obtaining accurate information, so that companies can prepare strategies that must be taken in certain circumstances. This requires the company to make reasonable planning for all production parameters, so that the company's profit expectations will always increase. In this study forecasting sales demand at PT. Candi Sugar Factory uses the Three Moving Average, Weighted Moving Average and Single Exponential Smoothing methods. The results of forecasting sugar sales in 2022 using the single Exponential Smoothing with = 0.35 is 19,894 tons.